ESSENCE AND CONTENT OF THE MAIN CONCEPTS THAT MAKE UP THE TERMINOLOGY APPARATUS OF MANAGEMENT OF INNOVATIVE DEVELOPMENT OF THE ENTERPRISE - SYDORCHUK, Ivanna (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article defines the essence of the concept of «innovative» and «development». The definitions of the innovative development of the enterprise were studied and their characteristics and signs were highlighted. The content of the concept of «innovative development of the enterprise» received further development, in which, among the known, attention is focused on the need to highlight the key elements and vectors of innovative changes for the formation of competitive advantages and maintaining the balance of relevant innovations in all structural and functional elements of the enterprise, which ensures the effect of synergy and increasing the development potential of the business entity.Innovations can be grouped into three groups: innovation as a process of qualitative changes; innovation as a result; innovation as a tool for creating new opportunities. That is, «innovative» is the one that is related to the process of qualitative changes, characterizes the result of invention and is aimed at creating new opportunities The main characteristics of the concept of «development» include: irreversibility, purposefulness, balance, manageability, progress, synergism, changes in quality. That is, development is a systemic concept that reflects the irreversibility of purposeful change to a qualitative state and balance. The main signs of innovativeness of development are: innovations (innovations), innovative processes, innovative activities and innovative potential (innovative resources). It should be noted that all scientists agree that the main feature of innovative development is innovation itself, as a certain catalyst, the basis of multifactorial changes.Summarizing the above, it can be stated that the innovative development of the enterprise is a compound and complex concept, which determines the expediency of its consideration from the standpoint of the signs of its innovativeness and actual development.
Keywords: innovation; innovative; development; innovative development of the enterprise